Synchronous bilateral Wilms tumor1. Issue 8 (10th January 2013) - Indolfi, Paolo; Jenkner, Alessandro; Terenziani, Monica; Crocoli, Alessandro; Serra, Annalisa; Collini, Paola; Biasoni, Davide; Gandola, Lorenza; Bisogno, Gianni; Cecchetto, Giovanni; Di Martino, Martina; D'Angelo, Paolo; et al.
Abstract BACKGROUND: The optimal management of bilateral Wilms tumor (BWT) is challenging, and their survival is lower than for unilateral tumors. This report discusses a large series of BWTs treated in Italy in the last 2 decades. METHODS: This analysis concerns patients with synchronous BWT registered at Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP) centers between 1990 and 2011; details on their treatment and outcome are presented and discussed. RESULTS: Ninety BWTs were registered in the AIEOP Wilms tumor database. Preoperative chemotherapy was given for a median 12 weeks before definitive tumor resection was attempted. Forty‐eight percent of the patients had preservation of bilateral renal parenchyma. The proportion of bilateral nephron‐sparing surgeries was not higher in the 37 patients initially given doxorubicin/vincristine/actinomycin D (32%) than in the 43 children receiving vincristine/actinomycin D alone (58%). The 4‐year disease‐free survival rate was 66.5% ± 5% and overall survival was 80% ± 5% for the cohort as a whole. The 4‐year disease‐free survival (overall survival) for 18 children with diffuse anaplasia or postchemotherapy blastemal‐type tumors was 51% ± 13% (62% ± 13%), as opposed to 72% ± 3% (88% ± 4%) for 68 children with a favorable histology (log‐rank P = .04 [P = .007]). CONCLUSIONS: These results provide further evidence that the optimal duration and choice of drugs for preoperative chemotherapy remain an open question. Outcome remained significantly worse for BWT than for unilateral Wilms tumor. To enable the conservative treatment of as many affected kidneys as possible, only centers with experience in BWT should manage such cases. Cancer 2013. © 2013 American Cancer Society.